2019
DOI: 10.3389/fnagi.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Chaperone-Mediated Protein Disaggregation and Proteolytic Pathways in Aging and Disease

Abstract: A functional protein quality control machinery is crucial to maintain cellular and organismal physiology. Perturbation in the protein homeostasis network can lead to the formation of misfolded and aggregated proteins that are a hallmark of protein conformational disorders and aging. Protein aggregation is counteracted by the action of chaperones that can resolubilize aggregated proteins. An alternative protein aggregation clearance strategy is the elimination by proteolysis employing the ubiquitin proteasome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…Additionally, Chapin et al reported that both basal autophagy as well as stress-induced autophagy can vary in different tissues [ 30 ]. Recently, it was shown that affecting proteostasis through the downregulation of chaperones involved in disaggregation results in increased autophagy and decreased UPS in C. elegans and human HEK293 cells [ 45 ]. Interestingly, the same study revealed that both autophagy and UPS are impaired in tissues expressing the human disease-linked amyloid protein Aβ 3–42 and Q 40 in C. elegans [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Chapin et al reported that both basal autophagy as well as stress-induced autophagy can vary in different tissues [ 30 ]. Recently, it was shown that affecting proteostasis through the downregulation of chaperones involved in disaggregation results in increased autophagy and decreased UPS in C. elegans and human HEK293 cells [ 45 ]. Interestingly, the same study revealed that both autophagy and UPS are impaired in tissues expressing the human disease-linked amyloid protein Aβ 3–42 and Q 40 in C. elegans [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that affecting proteostasis through the downregulation of chaperones involved in disaggregation results in increased autophagy and decreased UPS in C. elegans and human HEK293 cells [ 45 ]. Interestingly, the same study revealed that both autophagy and UPS are impaired in tissues expressing the human disease-linked amyloid protein Aβ 3–42 and Q 40 in C. elegans [ 45 ]. Here, we reveal that a widespread downregulation of distinct autophagy genes generates tissue-specific UPS responses.…”
Section: Discussionmentioning
confidence: 99%
“…Young adult animals expressing amyloid-β 3-42 or polyglutamine (Q 40 ) in neuronal cells show increased levels of LGG-1 and moderate increased levels of SQST-1 (sequestosome 1)/p62 via immunodetection, indicating impairment of autophagy [ 249 ]. Whether such an increase represents transcriptional induction of LGG-1 and SQST-1 was not examined.…”
Section: Neuronal Autophagy In Ageing: Insights From Caementioning
confidence: 99%
“…The insufficiency of the disaggregases has been linked with the amyloid-promoting propensity and its fatal consequences. 18 A functional prion protein (Sup35) that is beneficial to yeast serves as an excellent model to develop the prion concept as well as to elucidate the role of disaggregases in the prion-like transmission of several disease-associated amyloids. This is due to the following reasons.…”
Section: Introductionmentioning
confidence: 99%